Use of sargassum and other organic substitutes in the construction industry. A review - Cruz, Julio (2024)
Currently, sargassum, due to the large quantities that have arrived on the coasts of Mexico and other parts of the world, has become an environmental, economic and health problem, which makes its study important to provide value. Sargassum has been used for the production of biofuels and bioremediation, however, to the large amount of this organic material, the construction industry has used it in its raw state as a cementitious substitute. The objective of this article is to know the potential use of sargassum ash as a cementitious substitute, comparing it with various organic biomasses that have been used for the same purpose, for which a bibliographic review of organic biomasses, their characteristics, substitution percentages has been carried out. and its application. The above will provide knowledge of the properties that ash must contain for its application either in mortars or pastes that improve long-term durability, to advance sustainable construction.